Real‐life Use of Anticoagulants in Venous Thromboembolism With a Focus on Patients With Exclusion Criteria for Direct Oral Anticoagulants. Issue 4 (7th August 2017) - Moustafa, Farès; Pesavento, Raffaele; di Micco, Pierpaolo; González‐Martínez, José; Quintavalla, Roberto; Peris, Maria‐Luisa; Porras, José Antonio; Falvo, Nicolas; Baños, Pilar; Monreal, Manuel; ,
Abstract : We assessed the real‐life use of direct oral anticoagulants (DOACs) in patients with venous thromboembolism (VTE) and exclusion criteria for randomized trials. From 2013 to 2016, 3, 578 of 18, 853 patients (19%) had exclusion criteria. Irrespective of which anticoagulant was chosen, they had more VTE recurrences (hazard ratio (HR): 3.10; 95% confidence interval (CI): 2.47–3.88), major bleeds (HR: 4.10; 95% CI: 3.38–4.96), and deaths (HR: 9.47; 95% CI: 8.46–10.6) than those without exclusion criteria. During initial therapy, no patient with exclusion criteria on DOACs ( n = 115) recurred, but those on rivaroxaban bled less often (adjusted HR: 0.18; 95% CI: 0.04–0.79) than those on unfractionated heparin ( n = 224) and similar to those ( n = 3, 172) on low‐molecular‐weight (LMWH) heparin. For long‐term therapy, patients on rivaroxaban ( n = 151) had nonsignificantly fewer VTE recurrences (adjusted HR: 0.74; 95% CI: 0.08–1.32) and major bleeds (adjusted HR: 0.41; 95% CI: 0.15–1.15) than those on LMWH ( n = 2, 071). The efficacy and safety of DOACs were similar to standard therapy.